Heritability estimates of fractures in Japanese Thoroughbred racehorses using a non‐linear model. (21st February 2019) - Tozaki, Teruaki; Miyake, Takeshi; Kikuchi, Mio; Kakoi, Hironaga; Hirota, Kei‐ichi; Kusano, Kanichi; Ishikawa, Yuhiro; Nomura, Motoi; Kushiro, Asuka; Nagata, Shun‐ichi
Abstract: Thoroughbred racehorses are produced by mating small numbers of Arabian stallions and native British mares, and have been improved by selection of horseracing performance for about 300 years. While these improvements led to good performance as racehorses, they exposed horses to numerous medical disorders, aggravated by extensive exercise. Fractures are frequent medical disorders in Thoroughbred racehorses. In this study, fracture heritability was estimated using 3, 927 Japanese Thoroughbred racehorses to elucidate the risk of racehorse fractures. The heritability estimates of all examined fractures were low ( h 2 = 0.06), while those of fractures in carpal bone and carpus (carpal bone plus distal radius) were moderate ( h 2 = 0.37, 0.24, respectively). Fracture occurrence age for carpal bone and distal radius was both 3.3 years old and was younger than that for other fractures. These results indicated that a larger proportion of the variation in the studied population was due to genetic factors for carpal fractures than for other fractures, while the fractures at other bones were largely affected by environmental factors, correlated with the athlete period (number year in racing). These findings contribute to develop a management plan for suppressing racehorse fractures and improving horseracing safety.